The Influence of Highly Dispersed Metal Forms on Calcium and Phosphorus Metabolism in Polygastric Animals - Maratovna, Makaeva Ayna; Anatolevna, Sizova Elena; Nikolaevna, Atlanderova Ksenya (KnE Life Sciences, 2022)
Determining which forms of mineral feed additives can increase farm animal productivity is a key area of research. This study assessed the mineral composition of ruminal fluid and the effectiveness of calcium and phosphorus used by animals after the introduction of finely dispersed particles (FDP) of SiO2 (group I) and FeCo (group II) with a hydrodynamic radius of 109.6 ± 16.6 and 265 ± 25 nm, respectively. The deposition and use of calcium and phosphorus in the body of the experimental animals exceeded the control values. In group I, 30.8% more calcium was deposited (p ≥ 0.05), and in group II, the value was 30.3% (p ≥ 0.01). In the experimental groups, the calcium utilization rate was 27.3% higher in group I (p ≥ 0.05), and 28.2% higher in group II (p ≥ 0.01) compared to in the control. Phosphorus deposition was 34% higher (p ≤ 0.01) in experimental group I and 6% higher in experimental group II, compared with the control. Group I had a high utilization rate of phosphorus from the feed (with a 29% difference compared to the control). Comparison of the experimental groups revealed that the introduction of SiO2 FDP promoted an increase in the concentration of silicon, phosphorus, and calcium in the ruminal fluid. The introduction of FeCo FDP was accompanied by a decrease in the concentration of iron and cobalt in the ruminal fluid. Thus, the use of feed additive in finely dispersed form in the diet of animals was accompanied by an increase in the use of calcium and phosphorus by the animal’s body, which is advisable when intensifying milk and meat productivity. The obtained results require further research. Keywords: finely dispersed forms of microelements, ruminants, calcium and phosphorus exchange, feeding